An Evolutionary Critique of the Created Co-Creator Concept - Irons, William (Zygon, 2004)
The created co-creator theology states that human beings have the purpose of creating the most wholesome future possible for our species and the global ecosystem. I evaluate the human aspect of this theology by asking whether it is possible for human beings to do this. Do we have sufficient knowledge? Can we be motivated to do what is necessary to create a wholesome future for ourselves and our planet? We do not at present have sufficient knowledge, but there is reason to believe that with further scientific research we will be able to acquire it. The more difficult question is whether we can be motivated to cooperate on the scale necessary to fulfill this purpose. Evolutionary theories of human sociality, altruism, and cooperation are reviewed. I conclude that it is possible for human beings to fulfill the purpose defined for us by the created cocreator concept, but doing this will not be easy.